Determination of some metals in the commonly consumed dairy products randomly collected from the market in Alexandria - Egypt, with an emphasis on toxicity, permissible limits and risk assessment - Issa, Sahar; Genina, Doaa; Al Mazroua, Maha; Abdel Rahman, Safaa; M Fawzi, Marwa (International Journal of Pharmacology and Toxicology, 2016)
The aim of this research was to evaluate the possible contamination by heavy metals of 30 random samples of raw milk and four other dairy products (pasteurized milk, white cheese, yellow cheese, and yoghurt), that were purchased from the three different regions in Alexandria, Egypt namely; (Eastern, Central and Western Alexandria). Each sample was homogenized, powdered, and mineralized in a microwave oven. Quantitative analyses of Al, Se, Zn, Cd, Cu and Pb were performed using an inductively coupled plasma-mass (ICP-MS) spectrometry. Western Alexandria samples had the highest recorded levels in Pb, Cd and Cu (7.421 ppm, and 0.673 ppm, and 5.013 ppm) consecutively. Highest levels detected for Al and Se were detected in samples collected from Eastern Alexandria (2.74 ppm and 0.093 ppm) successively. Zn (31.64 ppm) showed the highest concentration in a sample purchased from Central Alexandria. Further investigations of the levels of metals in bigger number of milk samples from different zones of Alexandria, Egypt are necessary, both to examine this problem from the toxicological, clinical, and epidemiological point of view and, to assess the exposure risk.